Studi Kinerja Manajemen Konstruksi pada Proyek Pembangunan Kantor DPRD Sabu Raijua - Klau, Maria M. Julita; Rizal, A. Hidayat; Sina, Dantje A.T. (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2023)
In implementing a project, it is inevitable that various problems will slowly arise which will result in delays, decreased quality, and increased implementation costs. So this is a serious challenge, how will the problem be solved with the work system implemented so that the Sabu Raijua Regency DPRD office project can continue according to the initial plan. This study aims to determine the implementation of the construction management work system, determine the factors that influence the construction management work system and determine the actions that need to be taken in implementing the construction management work system using descriptive statistical analysis methods and quantitative analysis. The results showed that the perceptual analysis resulted in a percentage value of 63%. From the results of the analysis of the mean and IKR, it was found that the factors that influence the work system based on the most influential management functions are the evaluation, actuating, organizing, planning, and controlling functions. As for the actions that need to be taken in implementing work systems that are most influential based on management functions are the evaluation, organizing, planning, actuating, and controlling functions.